2022
DOI: 10.1007/s00330-022-09295-0
|View full text |Cite|
|
Sign up to set email alerts
|

Value of T2-weighted-based radiomics model in distinguishing Warthin tumor from pleomorphic adenoma of the parotid

Abstract: Objectives The differentiation of Warthin tumor and pleomorphic adenoma before treatment is crucial for clinical strategies. The aim of this study was to develop and test a T2-weighted-based radiomics model for differentiating pleomorphic adenoma from Warthin tumor of the parotid gland. Methods A total of 117 patients, including 61 cases of Warthin tumor and 56 cases of pleomorphic adenoma, were retrospectively enrolled from two centers between January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similar to the BT vs. MT studies, three studies indicated that models incorporating clinical and radiomics features outperformed those constructed using only clinical or radiomics features [15,22,25]. One study revealed that radiomics models comprising features extracted from multiple MRI sequences performed better than those utilizing a single sequence [22].…”
Section: Performances Of Radiomics Analysis In Characterizing Pa and Wtmentioning
confidence: 75%
See 1 more Smart Citation
“…Similar to the BT vs. MT studies, three studies indicated that models incorporating clinical and radiomics features outperformed those constructed using only clinical or radiomics features [15,22,25]. One study revealed that radiomics models comprising features extracted from multiple MRI sequences performed better than those utilizing a single sequence [22].…”
Section: Performances Of Radiomics Analysis In Characterizing Pa and Wtmentioning
confidence: 75%
“…MRI has also demonstrated comparable efficacy to FNAC in characterizing SGTs [9][10][11]. More recently, the introduction of radiomics analysis to medical imaging has brought new approaches for quantitative imaging analysis [12], so it is not surprising that researchers have investigated the performance of radiomics analysis in characterizing SGTs on MRI [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Although these studies showed that radiomics analysis offers great potential for characterizing SGTs on MRI, variations in the proposed radiomics models limit its application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Gabelloni et al ( 29 ) used a support vector machine classifier to differentiate between malignant and benign parotid neoplasms on T 2 WI, with high sensitivity (0.8695), specificity (0.9062), and accuracy (0.8909) in distinguishing PA from WT. However, the application of radiomics or deep learning is complicated and large datasets are required; image segmentation was based on visual inspection and manual delineation was time-consuming and laborious ( 32 , 33 ). The widespread application of radiomics in clinical practice needs to be further optimized.…”
Section: Discussionmentioning
confidence: 99%